If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 8 = 4x + -10 Reorder the terms: 8 + 3x = 4x + -10 Reorder the terms: 8 + 3x = -10 + 4x Solving 8 + 3x = -10 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 8 + 3x + -4x = -10 + 4x + -4x Combine like terms: 3x + -4x = -1x 8 + -1x = -10 + 4x + -4x Combine like terms: 4x + -4x = 0 8 + -1x = -10 + 0 8 + -1x = -10 Add '-8' to each side of the equation. 8 + -8 + -1x = -10 + -8 Combine like terms: 8 + -8 = 0 0 + -1x = -10 + -8 -1x = -10 + -8 Combine like terms: -10 + -8 = -18 -1x = -18 Divide each side by '-1'. x = 18 Simplifying x = 18
| 10x^2+9x-108=0 | | -2x^2+54x=0 | | 6(y-6)/10(y-6) | | H(5x)=3x^2+2 | | 2x^2+52x=0 | | 25x+16y=287.28 | | 2x^2+18x+162=0 | | -2(2x-4x)=6+18 | | 4=2k+22 | | (9y^2-8y+8)-(3y^2-8y+2)= | | -8b+3+6b=3b+8 | | x*1.618=60 | | 5y-8=-28 | | Y^2+18y+69=0 | | 28+9=2n | | 4x/5x-10=35 | | (3.99)2x+19.99y=111.88 | | 2r+12=6 | | -16t^2+25t+10= | | (4x^3-6x+7)=(-19x^3-15x-18) | | -16t^2+25t+8= | | 25x^2+75x-3250=0 | | 18x+94=10x+54 | | x^2-1132x+35200=0 | | u+10=v | | 1/20x=45 | | 8x+41=3x+27 | | 3x+15=2x+8 | | 23x+191=15x+119 | | k-2/17=8 | | 5x-11y=-2 | | 96/y=16 |